2007
DOI: 10.1021/es0715851
|View full text |Cite
|
Sign up to set email alerts
|

Do Potential Methylation Rates Reflect Accumulated Methyl Mercury in Contaminated Sediments?

Abstract: Relationships between the short-term mono-methyl mercury (MeHg) production, determined as the specific, potential methylation rate constant Km (day(-1)) after 48 h of incubation with isotope-enriched 201Hg(II) at 23 degrees C, and the long-term accumulation of ambient MeHg, were investigated in contaminated sediments. The sediments covered a range of environments from small freshwater lakes to large brackish water estuaries and differed with respect to source and concentration of Hg, salinity, primary producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
91
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 33 publications
14
91
1
2
Order By: Relevance
“…This greater anoxic character of the sediments seems to be essential to the occurrence of Hg methylation. In fact it is in this oxic/anoxic layer of the sediments that it is expected the highest activity of sulphate-reducing bacteria, which are the most important methylators for Hg, in a similar way as that observed by Drott et al [24] for sediments collected in several contaminated places. In this layer, bacteria are able to compete with respect to electron acceptors (such as O 2 , Fe(III)) and have access to energy-rich organic matter (electron donor).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…This greater anoxic character of the sediments seems to be essential to the occurrence of Hg methylation. In fact it is in this oxic/anoxic layer of the sediments that it is expected the highest activity of sulphate-reducing bacteria, which are the most important methylators for Hg, in a similar way as that observed by Drott et al [24] for sediments collected in several contaminated places. In this layer, bacteria are able to compete with respect to electron acceptors (such as O 2 , Fe(III)) and have access to energy-rich organic matter (electron donor).…”
supporting
confidence: 84%
“…In some studies, for example, Benoit et al [21] and Drott et al [24], the existence of a positive correlation between total Hg and MeHg is reported, suggesting that both Hg species (inorganic Hg and MeHg) were co-deposited or the in situ MeHg production was a function of total Hg concentration. In Largo do Laranjo, on the contrary, there were places with total Hg concentrations higher than those determined in site 1 and where MeHg was not detected.…”
Section: Monomethylmercury and Total Mercury Behavioursmentioning
confidence: 98%
“…Drott et al 2008). In the present study, since the MMHg PW / THg PW ratio was generally higher in the 0-1.5 cm layer than in deeper layers, the main production of MMHg likely occurs in the surface of sediments.…”
Section: Concentrations Of Sosupporting
confidence: 44%
“…These short-term measurements of potential rates of methylation and demethylation have been found to be unrelated to gross measures of long-term MeHg accumulation (Drott et al 2008;Johnson et al 2016). This suggests that these snapshot measurements may not be valuable in determining long-term process measurements.…”
Section: Why Is Net Methylmercury Production Important and How It Is mentioning
confidence: 95%
“…This suggests that these snapshot measurements may not be valuable in determining long-term process measurements. However, significant positive correlations have been found between K meth and %MeHg in many environments (Drott et al 2008), and %MeHg values in boreal wetlands tracked the ratio of K meth to K demeth (Tjerngren et al 2012a), suggesting that if both rates are measured, steady state net MeHg production rates can be estimated. Very recently, measurements of potential rates have been replaced with measurements of the genetic potential of the microbial community (e.g., Gionfriddo et al 2016) due to the recent discovery of a gene cluster responsible for mercury methylation (see below), and developments in this area will be useful in addressing many of the questions previously addressed using the measurements of potential rates.…”
Section: Why Is Net Methylmercury Production Important and How It Is mentioning
confidence: 99%